PENDEKATAN KONSELING PERSON-CENTERED BERBASIS NILAI ISLAM DALAM MENGATASI KESENJANGAN EMOSIONAL DALAM KELUARGA - Keti Yuliantika; Nurjannah (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2026)
This study aims to describe the effectiveness of individual counseling based on the Person-Centered approach integrated with Islamic values in addressing emotional deprivation resulting from a lack of emotional support within the family. This research employed a qualitative method with a case study approach involving a female client identified as NDF who experienced emotional distress related to family relationships. Data were collected through counseling interviews, observation of the client’s emotional responses during counseling sessions, and reflective documentation by the counselor. The counseling process was conducted in four sessions, including rapport building, problem identification, empathic confrontation, reframing, and evaluation. The findings indicate that the Islamic value-based Person-Centered approach effectively enhanced the client’s self-awareness, emotional regulation, emotional independence, and assertive communication skills. The integration of Islamic values such as sabr (patience), syukur (gratitude), and tawakkal (trust in God) strengthened the counseling process by providing a spiritual meaning framework for understanding emotional experiences. This study concludes that integrative counseling based on Islamic values contributes not only to reducing emotional distress but also to fostering sustainable psychological and spiritual well-being.   Keywords: person-centered counseling, Islamic values, family emotional support, emotional independence